Disentangling ecosystem services perception by stakeholders: An integrative assessment based on land cover. (July 2021) - Cabral, Pedro; Campos, Felipe S.; David, João; Caser, Ursula
Highlights: We assessed stakeholders' perception of ES supply in Portugal using CLC land cover. Drought regulation was ranked the most important ecosystem service. We show the potential impact of different scenarios on ecosystem service supply. Agriculture and forests/semi-natural areas provide two thirds of the total ES. Agriculture was considered the most important contributor to climate regulation. Abstract: Understanding where ecosystem services (ES) are and quantifying their supply using stakeholderś information is key for effective sustainable management. This paper describes a participatory methodology for extracting stakeholders' ES perception for continental Portugal based on land cover using analytical hierarchy process (AHP), matrix-based approach with data visualization techniques, and scenario analysis. Results show that drought regulation was the most valued ES by stakeholders and recreation was considered the least important. Results also show that the "Agricultural areas and "Forests and semi-natural areas" land cover classes provide about two-thirds of the total ES for the country. An "Economic development" scenario will yield negative values for all ES except recreation and food supply, whereas an "Environmental development" scenario will increase all ES, except food supply. Finally, a "Sustainable development" scenario, presents values between the previous two scenarios and is the best for food supply. This operational methodology for extracting information from stakeholders and to report information on the mapping and assessment of ES can be helpful for sustainable planning in Portugal and elsewhere.